2008
DOI: 10.1093/cercor/bhn134
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of the Expression of Dopamine D1 and D2 Receptors in Pyramidal and GABAergic Neurons of the Rat Prefrontal Cortex

Abstract: Mesocortical dopamine (DA) is a key neurotransmitter in cognitive processes and is involved in schizophrenia and antipsychotic drug action. DA exerts a highly complex modulation of network activity in prefrontal cortex (PFC), possibly due to the recruitment of multiple signaling pathways and to specialized cellular localizations of DA receptors in cortical microcircuits. Using double in situ hybridization, we quantitatively assessed the expression of D(1) and D(2) receptor messenger RNAs (mRNAs) in pyramidal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
172
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(187 citation statements)
references
References 64 publications
(83 reference statements)
15
172
0
Order By: Relevance
“…We would not necessarily expect to detect an overall D2 deficit because neuronal D2 receptors account for only a subset of total PFC D2 expression (32).…”
Section: Discussionmentioning
confidence: 97%
“…We would not necessarily expect to detect an overall D2 deficit because neuronal D2 receptors account for only a subset of total PFC D2 expression (32).…”
Section: Discussionmentioning
confidence: 97%
“…Dopamine has differentiated effects on dlPFC neuronal physiology in monkeys performing a spatial working memory task: D1/5R, but not D2/3R, stimulation influences Delay cell firing, whereas D2/3R, but not D1/5R, influences Response cell firing (Wang et al, 2004). This contrasts with rodent medial PFC, where certain physiologic studies find layer V neurons responding to both D1/5R and D2/3R manipulations (Parfitt et al, 1990;Zheng et al, 1999;Trantham-Davidson et al, 2004), although in situ hybridization studies have yet to definitively document coexpression within a single rodent PFC neuron (Santana et al, 2009). It is not known if this is a species difference or a regional difference (medial PFC versus dlPFC), because DA effects on medial PFC have yet to be studied in primates.…”
Section: Dopamine Influences On Dorsolateral Prefrontal Cortex Phymentioning
confidence: 99%
“…S4 F-H). We have previously shown that the AMPH locomotor response is mediated at least in part by D2Rs in a βarr2-dependent manner (27,29), but D2Rs are expressed in multiple regions of the brain, such as midbrain, STR, and PFC (24,(52)(53)(54)(55)(56)(57). To confirm which D2R+ population of neurons is responsible for the AMPH response, we deleted βarr2 in several distinct neuronal populations; βarr2 f/f mice were crossed with either D2Cre (all D2R+ neurons) or A2aCre (postsynaptic D2R+ striatal neurons) mice as well as the D1Cre (D1R+ neurons) or ChaTCre (cholinergic interneurons) mice as controls.…”
Section: Distinct Striatal Vs Cortical Role Of D2r On Pcp-mediated Bmentioning
confidence: 99%